1980
DOI: 10.1002/ange.19800920624
|View full text |Cite
|
Sign up to set email alerts
|

Hexakis(dimethylamino)cyclohexaboran, eine Bor(I)-Verbindung ohne Elektronenmangel

Abstract: Einen B6‐Ring in Sesselkonformation enthält die Titelverbindung (1), die aus Destillationsrückständen bei der Enthalogenierung von [(CH3)2N]2BCl kristallisiert. (1) ist der erste Homocyclus des Bors und zugleich die erste Bor(I)‐Verbindung ohne Elektronenmangel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
2

Year Published

1984
1984
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(13 citation statements)
references
References 17 publications
0
11
0
2
Order By: Relevance
“…[10] Boron compounds otherwise tend to form higher aggregated clusters rather than linear chains. [14] Recently, a B 4 R 4 chain was stabilized in the coordination sphere of a transition metal. [14] Recently, a B 4 R 4 chain was stabilized in the coordination sphere of a transition metal.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[10] Boron compounds otherwise tend to form higher aggregated clusters rather than linear chains. [14] Recently, a B 4 R 4 chain was stabilized in the coordination sphere of a transition metal. [14] Recently, a B 4 R 4 chain was stabilized in the coordination sphere of a transition metal.…”
mentioning
confidence: 99%
“…[11] Although hints were given for the existence of a linear B 8 (NMe 2 ) 10 com-pound, [12] the only structurally characterized longer derivatives are B 4 (NMe 2 ) 6 [13] and a cyclic species, B 6 (NMe 2 ) 6 . [14] Recently, a B 4 R 4 chain was stabilized in the coordination sphere of a transition metal. [15] All of the examples reveal the requirement of organic substituents for catenation.…”
mentioning
confidence: 99%
“…[1] This isomerization corresponds to the observation that crystals of 2b transform into 1b above 137°C. [2] In solution, however, cyclohexaborane 1b was reported to isomerize spontaneously into hypercloso-hexaborane 2b at room temperature.…”
Section: Syntheses and Nmr Spectroscopic Characterizationmentioning
confidence: 79%
“…[1] In 1991, Baudler et al described cyclohexaborane isomer 1b of B 6 (NEt 2 ) 6 as well as octahedral isomer 2b, the exact geometry of which could not be determined because of disorder of the crystals. [2] The same problem arose with 2b, which was prepared by the group of Siebert by a new route.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we observed the formation of the orange-red cyclo-hexaborane 7a in 1 % yield. 7a was first reported in 1980 [7]. Ten years later, the corresponding diethylamino derivative 7b was described, and it was found that on standing in solution the orange-red color of 7b changed to green [8].…”
Section: Cyclo-boranes and Polyhedral-boranesmentioning
confidence: 99%